A new norisoprenoid from the leaves of Ficus pumila. Issue 9 (3rd May 2019) - Bai, Meng; Cai, Yue; Wu, Shou-Yuan; Song, Xiao-Ping; Chen, Guang-Ying; Zheng, Cai-Juan; Han, Chang-Ri
Abstract: One new norisoprenoid 3, 9-dihydroxy dihydro actinidiolide (1 ), together with eleven known compounds (2–12 ), were isolated from ethanol extract of the leaves of Ficus pumila collected in Hainan Province, China. Their structures were elucidated by the detailed analysis of comprehensive spectroscopic data. Compounds1, 2, 4, 5, 8 and10–12 were isolated from the F. pumila for the first time. All compounds were evaluated for their cytotoxic activity. Compounds3 and9 showed weak cytotoxic activity against Hela, MCF-7 and A549 cell lines. Abstract :